Factors Associated With Grade 3 or 4 Treatment-Related Toxicity in Women With Advanced or Recurrent Cervical Cancer. Issue 2 (February 2015) - Chase, Dana M.; Kauderer, James; Wenzel, Lari; Ramondetta, Lois; Cella, David; Long, Harry J.; Monk, Bradley J.
<x xml:space="preserve">Abstract</x> Objective This study aimed to describe pretreatment patient characteristics and baseline quality-of-life scores as they relate to the development of grade 3 or 4 toxicity in patients receiving chemotherapy for advanced/recurrent cervical cancer. Methods The study sample was drawn from Gynecologic Oncology Group protocols 179 and 204. Grade 3 or 4 toxicities were considered in 4 specified categories as follows: peripheral neuropathy, fatigue, hematological, and gastrointestinal (GI). The data variables explored included age, stage, pretreatment radiation, performance status (PS) at treatment initiation, and baseline Functional Assessment of Cancer Therapy-Cervix (FACT-Cx) score. A logistic regression model was developed with various adverse events as binary (0/1) outcomes. Results Six hundred seventy-three patient-reported questionnaires were used in the analyses. At baseline, pain was the most severe patient-reported symptom. Baseline line-item patient concerns did demonstrate specific correlations with the development of individual toxicities. In 401 patients who were enrolled on Gynecologic Oncology Group 204 (fatigue not measured on 179), a worse PS predicted the development of grade 3 or 4 fatigue (odds ratio, 2.78; 95% confidence interval, 1.66–4.68). Exposure to previous radiation, treatment regimen, and a worse FACT-Cx score were associated with the reporting of both grade 3 or 4 leukopenia (P < 0.05) and anemia (P < 0.0005). Performance status and treatment regimen (P < 0.05) were associated with the development of grade 3 or 4 thrombocytopenia. Age and treatment regimen (P < 0.05) were associated with the development of grade 3 or 4 neutropenia. The FACT-Cx score (P = 0.0016) predicted grade 3 or 4 GI toxicity. Conclusions The development of fatigue, hematological, and GI toxicity might be predictable based on factors other than treatment assignment such as age, PS, and patient-reported quality-of-life measurement.